Environmental benefits and implicatons on nature - Shuriye, Abdi Omar (Islamic Centre for Education, Research and Development (ICERD), 2009)
As part of the universal arcangement to create harmonious coexistence berween man and other creatures the environment was made submissive to man by the Almighry. Man subsequently manages, uses and manipulates the environmenr for good or bad motives according to his conscious. Obviously when man develops this bounty he directly or indirectly opts to maltreatmenr on the natural conservation by being profligate and rapacious. To counter these natural tendencies of man the international conscious community developed ecotourism. As a concepr it signifies ecological tourism with both cultural and environmental undertone. It focuses on the tourist's treatment on the environment, the local cultures, wilderness adventures, volunreering and minimizing the adverse effect of conventional tourism on the natural environment and on the cultural integriry of the peopie. This section of the work evaluates the socio-environmental chailenges and Qur'anic outlook on the environment.